Internationalization of Banks European Cross-border Deals - Sist, Federica (Springer International Publishing, 2018)
This book reviews banking internationalization by considering the new paradigms of globalization. The author primarily analyses why and how banks internationalize through equity deals, and the effect of regulation and market integration on the formation of deals, which allows authorities to manage the banking structure. This is a unique work that describes the relevance of the ownership model and cultural features of the partners and the key factors that help in choosing the market in which the banks bring activities abroad. The book addresses market characteristics, and new scenarios that should impact banks' internationalization strategies and ability to achieve success in deals that capture the attention of both researchers and practitioners.